The one who declaims poems: The ritual nature of the poetic bonfire - S. S. Levochskiy; E. F. Levochskaia; A. M. Morozova (Шаги)
This article provides research into poetic bonfires, a collective reading practice in modern Russia, for example, the Marina Tsvetaeva bonfire and the Nikolay Rubtsov bonfire. On the popular poets’ death day or birthday, readers gather to read his or her poems and sing songs in a special place related to the poet’s biography. This practice is important in the context of reading practices and the formation and maintenance of a readers / reading community. The authors interpreted through the prism of cultural anthropology collected materials such as ethnographic diaries with thick descriptions and interviews. The authors make the assumption that poetic bonfires, with their ritualistic nature, are connected with the concept of cosmos (everything has to exist in right order). The cosmology of poetic bonfires is set through the repetition of behavioral templates, for example, reading poems and making the bonfire, and by semiotization of the area where the poetic bonfire takes place through the biography of the poet and the readers’ own poetry. Legitimization of the poetic bonfire depends on these factors, but at the same time, in most cases the poetic bonfire itself is informal. Therefore, the informal status of the poetic bonfire makes it a safe space and a special emotional refuge for the participants. The rituality that characterizes poetic bonfires allows participants to unite as a whole group with their own rules and behavioral models.